Analysis and Design of GAMERIK (Gamification of Computer Assembling) Based on PC Creator 2 in Improving Computer Assembling Skills: Analisis dan Desain GAMERIK (Gamifikasi Merakit Komputer) Berbasis PC Creator 2 untuk Meningkatkan Keterampilan Merakit Komputer - Nuryadi, Adi (Indonesian Journal of Innovation Studies, 2025)
General Background: In the digital era, technology has become an integral part of various aspects of life, including education. Specific Background: However, practice-based learning such as computer assembly continues to face challenges, including limited equipment, time constraints, and the risk of hardware damage. Knowledge Gap: Few instructional models effectively address these issues while providing a safe and engaging learning experience. Aims: This study aims to design a gamification-based learning model using the PC Creator 2 application to enhance students’ computer assembly skills. Results: The findings reveal that the gamified model significantly improves students’ motivation, engagement, and understanding of computer hardware concepts. Novelty: The innovation lies in integrating gamification into technical practice, allowing students to simulate assembling computers without the risk of damaging physical components. Implications: These results suggest that a gamification-based approach offers an effective and enjoyable solution for practical technology education and holds potential for broader application in vocational learning contexts. Highlights:    Enhances student motivation and engagement through game elements. Provides a safe, risk-free environment for technical practice. Bridges the gap in practical learning with innovative digital tools. Keywords: Gamification, Computer Assembly, Vocational Education, Digital Learning, PC Creator 2